Inhibition of the insulin-like growth factor 1 receptor by CHM-1 blocks proliferation of glioblastoma multiforme cells. (25th April 2015) - Lin, Ying-Chao; Hou, Shin-Chen; Hung, Chao-Ming; Lin, Jia-Ni; Chen, Wei-Chih; Ho, Chi-Tang; Kuo, Sheng-Chu; Way, Tzong-Der
Highlights: CHM-1 selectively blocked IGF-1R auto-phosphorylation. The phosphorylation of ERK1/2 and Akt was inhibited in CHM-1 treated GBM8401 cells. CHM-1P reduced the tumor volumes of the GBM8401 derived tumors in mouse brain. CHM-1 provided potential opportunities for effective chemotherapy for brain tumors. Abstract: The insulin-like growth factor-1 receptor (IGF-1R) plays a pivotal role in transformation, growth, and survival of glioblastoma multiforme (GBM) cells, and has emerged as a general and promising target for cancer treatment. In this study, we examined the anti-tumor effects of CHM-1, a synthetic 6, 7-methylenedioxy substituted 2-phenyl-4-quinolone derivative, on GBM cells in vitro and in vivo . CHM-1 selectively blocked IGF-1R auto-phosphorylation, with an ability to distinguish between IGF-1R and related tyrosine kinase receptors, such as insulin receptor (IR), epidermal growth factor receptor (EGFR), platelet-derived growth factor receptor (PDGFR), and fibroblast growth factor receptor (FGFR). Further investigation revealed that, the phosphorylation of ERK1/2 as well as Akt was inhibited in CHM-1 treated GBM8401 cells possibly through the selective blockage of IGF-1R auto-phosphorylation. Our study also showed that p.o. treatment with the hydrophilic dihydrogen phosphate CHM-1P reduced the tumor volumes of the GBM8401 derived tumors in mouse brain and also prolonged the survival rate. The results provided potential opportunities for effective chemotherapy for GBM.